INDONESIA’S INTERESTS IN THE COOPERATION ON DRUG AND VACCINE OVERSIGHT WITH THE UNITED ARAB EMIRATES IN 2021 - Zaharani Firdaushi; Slamet Muliono Redjosari (RADJA PUBLIKA, 2026)
This study examines how Indonesia articulates its national interests through bilateral cooperation in drug and vaccine regulatory oversight with the United Arab Emirates (UAE) in 2021. Using a qualitative descriptive approach, the research analyzes primary documents, including the Memorandum of Understanding (MoU) and official reports from the Indonesian Food and Drug Monitoring Agency (BPOM) and the Ministry of Health, supplemented by secondary sources. The study applies Andrew Moravcsik’s liberal intergovernmentalism framework, focusing on four indicators: consideration of domestic actors, bargaining among domestic actors, reflection of domestic preferences in international cooperation, and flexibility based on domestic dynamics. The findings indicate that Indonesia’s national interests are articulated through collaborative mechanisms that reflect the preferences and needs of diverse domestic actors, including government institutions, the health sector, industry stakeholders, and civil society. Policy decisions are the result of bargaining among these actors, ensuring that international cooperation aligns with domestic priorities such as technical capacity building, knowledge transfer, and public welfare. Furthermore, the MoU and related phenomena demonstrate that international agreements are not solely driven by geopolitical power, but by domestic considerations and mutual benefits, highlighting the adaptive and context-sensitive nature of Indonesia’s foreign policy in health regulation. This study contributes to a deeper understanding of how liberal approaches to national interest and intergovernmental cooperation shape international health policy, offering practical insights for policymakers to design flexible, inclusive, and sustainable international agreements in the health sector.